Transformation of Islamic Culture and Education: Between Modernization and Preservation of Islamic Values - Masnila Masnila; Syafe’i Syafe’i; Rifani Akhyar Qolbi; Komaruddin Komaruddin; Hilmin Hilmin (Lembaga Yasin AlSys, 2026)
Cultural transformation driven by globalization and modernization has profoundly affected multiple spheres of life, including Islamic education, compelling Islamic educational institutions to adapt in order to remain relevant amid rapid advances in science, technology, and information flows. At the same time, these modernization pressures pose challenges to preserving the core Islamic values that underpin the philosophy and practice of Islamic education. This study examines the dynamics of cultural transformation in Islamic teaching and analyzes strategies by which Islamic institutions can balance modernization imperatives with the preservation of Islamic values. Employing a library research methodology, it systematically reviews books, scholarly journal articles, and relevant documents on Islamic education and cultural change. The findings indicate that Islamic educational transformation need not be framed as a dichotomy between modernity and tradition; instead, it can adopt an integrative approach that selectively incorporates modern values and practices aligned with Islamic principles. Through such an approach, Islamic education can cultivate generations who are faithful and ethically grounded while also possessing the intellectual and social competencies needed to navigate global challenges without losing their Islamic identity.